Improved Proper Name Recall in Aging after Electrical Stimulation of the Anterior Temporal Lobes - Ross, Lars A.; McCoy, David; Wolk, David A.; Coslett, H B.; Olson, Ingrid R. (Frontiers in Aging Neuroscience, 2011)
Evidence from neuroimaging and neuropsychology suggests that portions of the anterior temporal lobes play a critical role in proper name retrieval. We previously found that anodal transcranial direct current stimulation (tDCS) to the anterior temporal lobes improved retrieval of proper names in young adult. Here we extend that finding to older adults who tend to experience greater proper-naming deficits than young adults. The task was to look at pictures of famous faces or landmarks and verbally recall the associated proper name. Our results show a numerical improvement in face naming after left or right anterior temporal lobe stimulation, but a statistically significant effect only after left-lateralized stimulation. The magnitude of the enhancing effect was similar in older and younger adults but the lateralization of the effect differed depending on age. These results provide evidence that tDCS may be a useful tool for the neurorehabilitation of cognitive function in healthy and pathological cognitive decline.